DEVELOPMENT OF THE EASTERN INDONESIA GREEN THERAPY CENTER AS AN ALTERNATIVE SOLUTION FOR SPECIAL NEEDS CHILDREN’S - Hayati, Riza Sativani; Sirajuddin, Sirajuddin; Ma'rifah, Destri Ratna (Jurnal Abdi Insani, 2024)
Green therapy, commonly known as nature therapy, is a method of stimulating children with special needs using natural media. Sekolah Alam Draul Istiqamah (SADIQ), one of natural school, has the potential to be developed as a green therapy center for Eastern Indonesia: (1) it has implemented the green therapy concept; (2) has sufficient open space; (3) has sports facilities that have potential for therapy; (4) not far from Makassar Sultan Hasanuddin Airport which can be reached in approximately 10 minutes; (5) have a good safety guarantee for the green therapy program. This potential has not been used properly for the development of green therapy centers due to limitations, including: (1) limited knowledge and skills of human resources in terms of developing green therapy centers; (2) the need to prepare a good concept to become a green therapy center, starting from the type of service program, natural therapy activities in each service, therapy guides, and the stimulation media needed; (3) There is no media to introduce SADIQ as a green therapy center for the community. The solutions offered for SADIQ to be developed as a Green therapy center include: (1) Green therapy education for SADIQ human resources in the form of training, practice and workshops; (2) provision of standard facilities to support the perfection of the types of stimulation services to be provided; (3) preparing a green therapy service program starting from the name of the program to the stimulation activities that must be carried out; (4) preparation of green therapy service program guidelines; (5) outreach and offering to the public and educational practitioners; (6) assisting the implementation of service programs at the green therapy center. This series of activities proved effective in increasing the understanding and practice of green therapy among SADIQ human resources, was able to introduce SADIQ as a green therapy center in Eastern Indonesia, and brought SADIQ recognition from stakeholders, especially the Education Department. SADIQ is currently an alternative solution in providing green therapy, alternative solution of special need children stimulation through natural media.